Legal Protection of Coastal Community Land Tenure Rights - Anis Mashdurohatun; Abdul Hanis Embong (Contrarius, 2025)
Indonesia has established numerous legal frameworks governing land ownership and land use in coastal areas; however, ineffective enforcement, overlapping institutional authorities, inconsistent regional implementation, and limited protection of community rights continue to undermine their effectiveness. This study examines the regulation and management of land tenure rights for coastal communities and identifies normative weaknesses that generate legal uncertainty and social injustice. The research applies a normative juridical method, employing statutory, conceptual, and comparative approaches, with a focused comparison on the Philippine legal framework. The findings reveal that unequal access to land, fragmented institutional authority, and the dominance of a legalistic-positivist regulatory paradigm actively marginalize coastal communities, particularly indigenous peoples, and expose them to a heightened risk of displacement. By contrast, the Philippines adopts an integrated and participatory legal approach that positions coastal and indigenous communities as primary stakeholders in natural resource governance through constitutional recognition, public land regulation, indigenous rights protection, and fisheries management. This framework strengthens community participation through community-based coastal resource management and promotes shared responsibility for ecosystem sustainability. The study concludes that Indonesia must reform its coastal land tenure regulations by adopting a rights-based and participatory legal approach that enhances legal certainty, advances social justice, and ensures a balanced relationship between environmental protection and the socio-economic sustainability of coastal communities.